Pore-Level Interpretation of Methane Hydrate Growth and Dissociation with Deionized and Saline Water - Iden, Eirik Johan (The University of Bergen, 2017)
Natural gas hydrates are solid crystalline compounds composed of water and gas molecules, located in vast amounts around the world, in subsurface permafrost and oceanic environments. With an increasing demand of energy worldwide, methane production from natural gas hydrates may play an important role to ensure future energy sustainability. Research on methane hydrate on pore-level may contribute to a greater understanding of the fundamentals and characteristics of hydrate formation and production schemes. This thesis presents a series of experiments conducted in a two-dimensional synthetic micromodel. The main objective of the experiments was to determine and interpret methane hydrate characteristics on pore-level using microscopy, during hydrate formation and dissociation with different water solutions. In the experiments, deionized water and saline water of 2.0, 3.5 and 5.0 wt% sodium chloride (NaCl) were used. The saturation changes for water, gas and hydrate were estimated to determine water and gas behavior in each experiment. There were conducted 16 successful hydrate formations, where ten were primary formations and six were secondary formations. During primary hydrate formation, the temperature and pressure values were fixed, and hydrate growth was induced by forcing agitation on water and gas in the micromodel. The temperature was in the range 1.0-4.1°C, and the pressure was in the range 80.0-110.0 bar. During secondary hydrate formation, the temperature was approximately 4.0°C, and the pressure was increased to above the hydrate stability line. Primary hydrate formation was faster and more homogeneous than secondary hydrate formation, independent of water salinity. Hydrate growth occurred mainly within the gas, but was one time observed to occur in the water phase. Initial hydrate growth occurred on the water-gas interface at the pore walls and continued to grow in the gas towards the pore center. Salt was the limiting factor when hydrate was being formed with saline water of 3.5 wt% NaCl and higher, ...